The Potential of Cooling Effect Using Palm Oil Clinker as Drainage Layer in Green Roof System - Khairul Anuar, Shahid; Sharifah Maszura, Syed Mohsin; Norhaiza, Ghazali (2015)
Research on green roof has been quite intensive in the past decade. Many researchers have studied on the cooling effect of green roof without focusing on an alternative to replace the conventional material in green roof system. The needs to use waste material become more essential to ensure the environmental sustainability. Hence, this paper reports on the use of palm oil clinker as drainage layer in green roof system and also the cooling potential of green roof under Malaysia climatic condition. Hydraulic conductivity was investigated through constant load permeameter test and the cooling effect was studied by means of experimental green roof in cubicles. The analysis of thermal performance was carried out by using CLTD/CLF/SCL method. It was found that palm oil clinker is suitable to replace conventional materials as drainage layer in green roof system and it is also found that the green roof could reduce the air temperature inside the experimental cubicles hence reduced the heat gains